Fear and level of preparedness of medical care workers post lockdown in the realms of COVID-19 pandemic - Sibal, Prabhleen Kaur; Holla, Sadhana Nittur; Holla, Sarika Nittur (Intelektual Pustaka Media Utama, 2023)
The COVID-19 outbreak had placed an exceptional demand on the health system. They were flooded by an overabundance of activities related to controlling the pandemic. There was a need to conduct a study which acknowledged the fear and requirements of medical care workers to handle the patient load and not compromise on delivering health services to the public. This study was cross-sectional, observational with an online questionnaire based on framework provided by the centres for disease control and prevention, preparedness tools for healthcare professionals, facilities and how to cope with stress and build resilience during the COVID-19 pandemic. Majority of healthcare workers were doctors, interns and nurses under age group of 18-24. There was a significant association between health profession and preparedness of situation and preparedness of workplace. Majority were aware of COVID-19 treatment guidelines, received training in using personal protective equiment and were ready to isolate if there was contact with COVID-19 patient. Doctors held a fear of contacting the disease. Frontline workers, aged 45 years and less, females and married individuals expressed greater concerns of fear of disease at their workplace. Medical care workers at the frontline fighting the pandemic are more vulnerable and preparedness of the staff in health-care settings are crucial.